CORPORATE SOCIAL AND ENVIRONMENTAL RESPONSIBILITIES IN THE ARCTIC ZONE OF THE RUSSIAN FEDERATION : THEORETICAL AND METHODOLOGICAL APPROACHES - Bobylev, Nikolai; Gadal, Sébastien; Sergunin, Alexander; Tynkkynen, Veli-Pekka (Корпоративное управление и инновационное развитие экономики Севера, 2022)
Peer reviewed